Maturity‐onset diabetes of the young (MODY) due to PDX1 mutation in a sib‐pair diabetes family from Qatar. Issue 12 (11th December 2021) - Haris, Basma; Mohammed, Idris; Syed, Najeeb; Fakhro, Khalid; Hussain, Khalid
Abstract: Maturity‐onset diabetes of young (MODY) is an autosomal dominant genetic disorder that causes insulin deficiency without autoimmunity. We present the first family with pancreatic duodenal homeobox 1 (PDX1) mutation causing diabetes from Qatar. Routine genetic screening of all antibody‐negative diabetic patients with diabetes should be offered to avoid misdiagnosis. Abstract : We report the first family with PDX1 mutation causing diabetes in children from Qatar and present a complex pedigree which is contributing to the disease condition. Efforts to implement precision medicine for all patients with antibody‐negative diabetes will bring better clinical outcomes.